Wpływ reklam telewizyjnych na psychikę dzieci i ich wychowanie we współczesnej rodzinie - Michał Jóźwik (Wrocławski Przegląd Teologiczny)
The TV picture – moving and colorful has a “magnetic” effect that evokes an orientation reflex, it fixes automatically the eyesight on the screen. The usage of the television and other media changes the socialization and upbringing process of the children in the families.Watching TV by virtue of its universality and attractiveness becomes for many families an integral part of family life and the most popular method of spending of free time. The commercials are an extremely attractive entertainment method because of the way how their content is presented. It is the reason why children like watching them. The aim of this article is an attempt to present responses for question about the influence of TV commercials on development of children’s psyche and their upbringing in the contemporary family.